Antioxidant and Anti-Obesity Properties of Acidic and Alkaline Seaweed Extracts Adjusted to Different pH Levels - Sakhi Ghelichi; Mona Hajfathalian; Sara Falcione; Charlotte Jacobsen (Marine Drugs)
This research examined antioxidant and anti-obesity effects of Palmaria palmata extracts obtained through acidic or alkaline treatments and subsequent pH adjustments. After two rounds of acidic or alkaline extraction, the extracts were separated from biomass and adjusted to different pH values: for acidic extracts, pH 3 (no adjustment), pH 6, pH 9, and pH 12; for alkaline extracts, pH 12 (no adjustment), pH 9, pH 6, and pH 3. The findings revealed that extraction medium as well as subsequent pH adjustments significantly influenced composition of the extracts in terms of protein content and recovery, amino acids, and phenolic compounds (p < 0.05). Acidic conditions produced extracts with potent radical scavenging, especially at pH 6 (IC50 = 0.30 ± 0.04 mg.mL−1), while alkaline conditions favored metal chelating, with the highest Fe2+ chelation at pH 12 (IC50 = 0.65 ± 0.03 mg.mL−1). Moreover, extracts showed inhibitory activities against porcine pancreatic lipase and α-amylase, with the acidic extract at pH 9 showing the best anti-obesity properties (IC50 = 5.38 ± 0.34 mg.mL−1 for lipase and IC50 = 5.79 ± 0.30 mg.mL−1 for α-amylase). However, the highest α-amylase activity was in the alkaline extract at pH 12 (IC50 = 3.05 ± 0.66 mg.mL−1). In conclusion, adjusting the pH of seaweed extracts notably influences their bioactive properties, likely due to changes in the reactivity and interactions of bioactive compounds such as peptides, carbohydrates, and polyphenols.